2022 Crisis Preparedness Training: Annual Report. Issue 12 (23rd December 2022) - Johnson, Julia; Vincent, Andrew
Abstract: During 2022, the European Food Safety Authority (EFSA) organised 2 crisis preparedness training events: 1 event involving European Union (EU) Member States (MSs) and EU candidate countries (designated the External Crisis Preparedness Training or ECPT); and another event dedicated to EFSA colleagues (designated the Internal Crisis Preparedness Training or ICPT). The selected scientific domain for both training events was chemical contamination, with a fictional scenario focusing on heavy metal contamination of a foodstuff forming the focus for the simulation exercise elements during both events. The external event was organised in conjunction with the Bulgarian Risk Assessment Centre on the Food Chain (RACFC) and took place over 3 days in Sofia, Bulgaria. The internal event was a day‐long session at EFSA's offices in Parma, Italy. EFSA's crisis training contractor, Instinctif Partners, co‐organised both events. In addition to simulation exercise elements, both events also included informational presentations relating to chemical contamination of the food chain; facilitated discussions on crisis response topics; plus practical training and rehearsal on EFSA tools and/or procedures. The objectives of each event were achieved, based on recorded outcomes and feedback provided by participants in an evaluation survey completed at the end of each event.